Temporal Relationship Between Onset of Fever and Development of Cerebral Vasospasm and Poor Functional Outcome in Aneurysmal Subarachnoid Haemorrhage. (16th November 2020) - Saripalli, Manasa; Tan, Darius
Abstract: INTRODUCTION: Aneurysmal subarachnoid haemorrhage (aSAH) resulting from rupture of intracerebral aneurysms accounts for approximately 4% of strokes. Cerebral vasospasm is the leading cause of poorer outcome and higher global disease burden following aSAH. The incidence of postoperative fever in aSAH patient is 70%. Although it has extensively been shown that fever is associated with poor clinical outcomes, the relationship between fever and development vasospasm is poorly understood. METHODS: A retrospective cohort study of 183 consecutive patients who were treated for aSAH at our institution between July 2015 and January 2020 were reviewed. 2 hourly temperature readings for individual patient from ictus through to day 14 post admission were recorded. Receiver operator curves were generated for each day to identify threshold temperatures which predict the two primary end points, cerebral vasospasm and poor outcome (mRS>2). Fever was defined as a temperature ≥38°C. Vasospasm was defined as patients with clinical deterioration (i.e. decreased GCS) who underwent CT brain and angiogram and perfusion protocols to confirm radiographic spasm. To identify potential risk factors, univariate and multivariate regression models were constructed for both endpoints. RESULTS: One hundred and eighty-three patients were identified (130 female and 53 male); their median age at diagnosis was 55.8 years (range 20.5 to 87.2 years). Fever was recorded in 109 (59.6%) patients, of which, 29.5% had no recognizable source of infection. The onset of central fever and fever of any aetiology on day 4 post ictus independently predicted the development of cerebral vasospasm (OR 2.91 95% Cl 1.06-7.96, P = . 002; OR 2.20 95% Cl 1.05-4.62, P = . 038 respectively). The presence of fever beyond day 7 post-ictus independently predicted unfavourable outcomes following aSAH (OR 9.83 95% CI 3.60-26.84, P = . 000). CONCLUSION: Early development of fever on day 4 post ictus suggest increased risk of impending vasospasm, and persistence of fever beyond day-7 ictus suggest increased risk of poor clinical outcomes. Additionally, two-hourly mean temperatures are consistently elevated in patients with vasospasm beyond day 4.